Soil fertility cultivated with conilon coffee after application of treated wastewater - Gonçalves, Ivo Zution; Garcia, Giovanni Oliveira; Rigo, Michelle Machado; dos Reis, Edvaldo Fialho; Tomaz, Marcelo Antonio (Coffee Science - ISSN 1984-3909, 2014)
At present the need for water and nutrients in agriculture is increasing, and this can become a problem because the high cost of fertilizers and low supply of water resources, requiring alternative sources of water and nutrients to maintain agricultural production. With the objective of evaluating the inputs nutrients and fertility soil after application of treated wastewater in an Oxisol cultivated with conilon coffee, an experiment under greenhouse conditions was carried out, from November 2010 until January 2011. The experiment was realized on a split-plot 13 x 4, with thirteen clones in plots and in the sub-plots three depths of domestic sewage, applied with a third, two-thirds and 100% of the crop water demand total, and a control level with water supply, in a completely randomized design with three replicates. Were evaluated the input nutrient soil by wastewater and its efficiency as nutritional source to coffee tree. There was an increased of the salinity soil, however, there was increased of magnesium, potassium, base saturation, sum of bases with application of treated wastewater, and thus, it’s concluded that the treated wastewater can reduce spending on fertilizers in the initial cultivation of conilon coffee tree.